The Influence of 'Santri Identification' on the Choice of Presidential and Vice Presidential Candidates Based on Religion in the 2024 Presidential Election - Amir Mahmud; Dewien Nabielah Agustin (PT Pro Panoramic Solution, 2025)
The phenomenon of the power of figures as a voter getter in democracy impacts the selection of candidates who will be nominated in the general election contest. Candidate pairs are not seen based on their abilities, but rather on how the candidates can win the general election. The use of figures as a means of attracting voters can be seen from the nomination of presidential and vice presidential candidate pairs in the 2024 presidential election. Two of the three candidate pairs have brought together figures from Nahdlatul Ulama as candidate pairs as a winning strategy. In the discipline of socio-political science, a person's voting behavior in a general election is not just a five-yearly activity; there are reasons and backgrounds as to why someone chooses a particular pair. This study aims to analyze more specifically the influence of Islamic boarding school identification on the choice of presidential and vice presidential candidates based on religion. This study uses a survey method with a correlational approach. The subjects in this study were students of the Al-Amien Islamic boarding school with a sample size of 207 students. The results of the analysis show that Islamic boarding school identification has a significant influence on voting behavior. However, the magnitude of the contribution of santri identification is relatively weak, reflected in the regression coefficient of 0.07, while the rational consideration variable, which includes the evaluation of the vision, mission, programs, and track records of the candidates, is proven to have a more substantial influence, with a regression coefficient reaching 0.43. Based on these findings, it can be concluded that although santri identification contributes to santri political preferences, rational considerations play a more dominant role in their decision-making process.